2018
DOI: 10.1001/jamaophthalmol.2017.4003
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Patient With T-Cell Lymphoblastic Lymphoma and Acute Vision Loss

Abstract: A 16-year-old girl with a history of T-cell lymphoblastic lymphoma and stem cell transplant presented with blurry vision in the left eye. One day prior, she developed a new-onset right facial palsy in addition to bilateral eyelid, lip, and feet swelling. Ophthalmologic evaluation revealed visual acuities of 20/20 OD and 20/800 OS. The left eye showed a relative afferent pupillary defect and decreased color vision. Extraocular movements, confrontation visual fields, and intraocular pressures were within normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Bidar et al reported that leukaemia was eventually diagnosed in around 11% of children who initially presented with unilateral ptosis [7]. Given the wide range of structures involved, these lesions may manifest in a myriad of different ways, from asymptomatic presentations to proptosis and orbital swelling which may be unilateral, bilateral, painful or even painless to chemosis, diplopia, decreased vision, or blindness [14][15][16][17]. A formal ophthalmologic examination in all patients with leukaemia is prudent.…”
Section: Discussionmentioning
confidence: 99%
“…Bidar et al reported that leukaemia was eventually diagnosed in around 11% of children who initially presented with unilateral ptosis [7]. Given the wide range of structures involved, these lesions may manifest in a myriad of different ways, from asymptomatic presentations to proptosis and orbital swelling which may be unilateral, bilateral, painful or even painless to chemosis, diplopia, decreased vision, or blindness [14][15][16][17]. A formal ophthalmologic examination in all patients with leukaemia is prudent.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the optic nerve can be the site of CNS relapse in leukemia and lymphoma, despite presumed systemic and medullary remission (5,(10)(11)(12). Although most optic neuropathy cases occur in the setting of preexisting CNS disease, there are cases in which leukemic optic neuropathy is the first manifestation of CNS involvement (2)(3)(4)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…O ptic neuropathy in the context of leukemia and lymphoma can be attributed to infectious, inflammatory, infiltrative, ischemic, or toxic-metabolic etiolo-gies (1). Because the optic nerve is a direct extension of the central nervous system (CNS), the finding of optic nerve dysfunction in patients with leukemia or lymphoma raises concern for CNS involvement or relapse, thus warranting prompt evaluation and treatment (2)(3)(4)(5)(6)(7)(8). Even in the setting of prompt management, leukemic optic neuropathy carries a poor visual prognosis and many patients ultimately progress to optic atrophy and death (9).…”
mentioning
confidence: 99%